DEVELOPMENT OF KALIKA (FIVE CHARACTER CARDS) LEARNING MEDIA ON THE CLASSIFICATION OF LIVING THINGS USING THE DESIGN THINKING FRAMEWORK - Fitriyyah, Putri Nurul; Samsudin, Achmad; Solihat, Rini; Winarno, Nanang; Tarliyah, Lea (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2024)
Learning media is one of the important things of learning tools that can increase students’ interest in learning. This study aims to develop KALIKA (Five Character Cards) learning media on the classification of living things using the Educational Design Research (EDR) method to enhance student achievement. The development model refers to ADDIE with a design thinking framework. The research was carried out at one of the Junior High School in Bandung City, during the even semester of 2023/2024, with a focus on students in class VII, totaling 21 participants. Convenient sampling was utilized for subject selection. The data collection techniques in this research data are validation sheet, assessment formative (pretest and posttest), and questionnaire user response. The validation sheet and user response questionnaire were processed into percentage data using Microsoft Excel, while the formative test results were processed using the Wilcoxon Signed Rank Test statistical test and N-gain using SPSS. The results of this study showed that the validation test data obtained a validity percentage of 92.4% which categorized as very valid criteria, the Wilcoxon Signed Rank Test results state p <0.05 which means there is a significant difference between the pretest and post-test, and the results of the effectiveness test with N-gain effectiveness results of 0.31 which means the effectiveness of student learning is in the moderate category, and 95% students give positive response to KALIKA as learning media. This shows that using KALIKA learning media is quite effective as a support to improve student learning outcomes on the classification of living things. Previous researchers have never developed card-learning media using ADDIE with a design thinking framework, which contains five characters of 5 kingdoms of living things.